PERAN GURU DAN ORANG TUA DALAM LITERASI BAHASA SISWA KELAS II DI SDN 5 DANGER - Mery Dwi Rahmawati; Moh. Irawan Zain; Syaiful Musaddat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to determine the role of teachers and parents in language literacy of grade II students at SDN 5 Danger. This study uses a descriptive qualitative approach. Data collection techniques used are observation, interviews, and documentation. Data analysis used the data analysis model from Milles and Huberman which started from data reduction, data presentation, and drawing conclusions. The results showed that the second grade teacher at SDN 5 Danger had a good role in language literacy. This can be seen from literacy planning, literacy implementation, and the results of literacy implementation which have increased, making the teacher's role very important in literacy activities, while parents of class II SDN 5 Danger have also played a good role in relation to language literacy. This can be seen from literacy planning, literacy implementation, and the results of literacy implementation which have increased. This is also evidenced by the contribution of parents starting from making literacy schedules, providing facilities, and accompanying children in literacy activities.